Learning package on parent education on adolescent health and development - Philipines. Commission on Population (Mandaluyong City : Popcom, 2008)
Content: Module 1: me as a parent -- Module 2: me and my family
Keywords: Parenting; Adolescent Health; Adolescent Development; Teaching Materials